Remember where you came from: ABA insensitivity is epigenetically inherited in mesophyll, but not seeds. (June 2020) - Negin, Boaz; Moshelion, Menachem
Highlights: Insensitivity to ABA is epigenetically inherited in mesophyll, but not seeds. Epigenetically ABA-insensitive plants maintain many parental phenotypes. The inherited phenotypes remain stable for at least three generations. Abstract: Plants transmit their experiences of environmental conditions to their progeny through epigenetic inheritance, improving their progeny's fitness under prevailing conditions. Though ABA is known to regulate epigenetic-modification genes, no strong phenotypic link between those genes and intergenerational "memory" has been shown. Previously, we demonstrated that mesophyll insensitivity to ABA ( FBPase::abi1-1fa transgenic plants) results in a range of developmental phenotypes, including early growth vigor and early flowering (i.e., stress-escape behavior). Here, we show that null plants, used as controls (segregates of FBPase::abi1 that are homozygote descendants of a heterozygous transgenic plant, but do not contain the transformed abi1-1 gene) phenotypically resembled their FBPase::abi1-1 parents. However, in germination and early seedling development assays, null segregants resembled WT plants. These FBPase::abi1-1 null segregants mesophyll-related phenotypes were reproducible and stable for at least three generations. These results suggest that the heritability of stress response is linked to ABA's epigenetic regulatory effect through ABI1 and mesophyll-related traits. The discrepancy between the epigenetic heritability of seed and mesophyll-related traits is an example of the complexity of epigenetic regulation, which is both gene and process-specific, and may be attributed to the fine-tuning of tradeoffs between flowering time, growth rate and levels of risk that allow annual plants to optimize their fitness in uncertain environments.